Antinociceptive, anti-inflammatory and antipyretic properties of Melastoma malabathricum leaves aqueous extract in experimental animals - Zakaria, Zainul Amiruddin; Raden Mohd Nor, Raden Nur Suraya; Gopalan, Hanan Kumar; Abdul Ghani, Zuleen Delina Fasya; Sulaiman, Mohd Roslan; Ganeson, Rathna Devi; Mat Jais, Abdul Manan; Somchit, Muhammad Nazrul; Abdullah, Fatimah Corazon (NRC Research Press, 2006)
The present study was carried out to establish the antinociceptive, anti-inflammatory, and antipyretic properties of the aqueous extract of Melastoma malabathricum leaves in experimental animals. The antinociceptive activity was measured using abdominal constriction, hot-plate, and formalin tests, whereas the anti-inflammatory and antipyretic activities were measured using carrageenan-induced paw edema and brewer’s yeast-induced pyrexia tests, respectively. The extract, which was obtained after soaking the air-dried leaves in distilled water for 72 h and then preparing in concentrations of 10%, 50%, and 100% (v/v), was administered subcutaneously 30 min prior to subjection to the above mentioned assays. At all concentrations tested, the extract was found to exhibit significant (P < 0.05) antinociceptive, anti-inflammatory, and antipyretic activities in a concentration-independent manner. Our findings that the aqueous extract of M. malabathricum possesses antinociceptive, anti-inflammatory, and antipyretic activities supports previous claims on its traditional uses to treat various ailments.